THU0215 Long-Term Efficacy and Safety of Canakinumab in Patients with Systemic Juvenile Idiopathic Arthritis (SJIA): 5-Year Follow-up of An Open-Label Trial. (15th July 2016) - Ruperto, N.; Brunner, H.I.; Quartier, P.; Constantin, T.; Alexeeva, E.; Schneider, R.; Kone-Paut, I.; Schikler, K.; Marzan, K.; Wulffraat, N.; Padeh, S.; Chasnyk, V.; et al.
Abstract : Background: SJIA is a distinct and debilitating form of arthritis associated with elevated cytokine (interleukin [IL]-1 and IL-6) levels. 1 Studies have shown that biologics (IL-1 and IL-6 inhibitors), including canakinumab (CAN), a selective, human anti-IL-1β monoclonal antibody, are more effective than conventional medications (NSAIDs, corticosteroids, methotrexate) in the treatment of SJIA patients (pts). 1, 2 However, little is known about long-term efficacy and safety of biologics in SJIA. Objectives: To assess long-term efficacy and safety of CAN treatment in a 5-year (yr) follow-up of SJIA pts. Methods: This was an open-label extension study of SJIA patients participating in the clinical trials of CAN, with details reported earlier. 3 Pts (age, 2–20 yrs) received subcutaneous (sc) CAN (4 mg/kg) every 4 wks. Baseline is defined as the starting point of the extension trial. Efficacy measurements were done every 3 months including adapted paediatric response criteria (aACR), clinical inactive disease, clinical remission on medication (12 months of continuous clinical inactive disease) and juvenile arthritis disease activity score (JADAS). Safety was assessed monthly. Results: Overall, 147 pts had a median treatment duration of 3.2 yrs, and 82 (56%) were exposed to CAN for >3 yrs (total treatment exposure of ∼365 pt-yrs). At 3 month of CAN therapy, 50% of pts had inactive disease, increasing to 49% at last assessment. Of the 107 pts with an aACR 30 at entry to the extension, 61.7% had aACR 100, with 86.0%, 87.9% and 91.6% having aACR 70/50/30 responses, respectively at last assessment. Clinical remission on medication was achieved in 43.0% of pts. Median JADAS10-CRP at baseline was 8.2 (indicating moderate disease activity), and at last assessment, median change from baseline was −0.2, with a median score of 1.8, indicating low disease activity, with similar results noted for JADAS27-CRP. Most common adverse event (AE) was infection (2.0 infections/100 pyr) typically involving the upper respiratory tract. Overall, 47 (32.0%) pts had >1 serious AE (SAE; mostly infections, macrophage activation syndrome [MAS] or SJIA flare), 10 cases of MAS (43.8 events/100 pyr) were reported, and 18 (12.2%) pts discontinued due to an AE. No deaths were reported. Conclusions: In patients previously treated with CAN in pivotal trials, response to treatment was sustained or improved during long-term treatment in the extension study. Safety profile of CAN was consistent with safety findings from previous studies. References: Ruperto N, et al. N Engl J Med. 2012;367:2396–406. Ringold S, et al. Arthhritis & Rheum. 2013;65(10):2499–512. Ruperto N, et al. Ann Rheum Dis. 2015;74(2):608. Disclosure of Interest: N. Ruperto Grant/research support from: Abbott, BMS, "Francesco Angelini", GlaxoSmithKline (GSK), Hoffman-La Roche, Italfarmaco, Janssen, Novartis, Pfizer, Sanofi Aventis, Schwarz Biosciences, Sobi, Xoma, Wyeth, Speakers bureau: Abbott, AbbVie, Amgen, Biogenidec, Astellas, Alter, AstraZeneca, Boehringer, BMS, CD-Pharma, Celgene, CrescendoBio, EMD Serono, Hoffman-La Roche, Italfarmaco, Janssen, MedImmune, Medac, Novartis, Novo Nordisk, Pfizer, Sanofi Aventis, Servier, Takeda, Vertex, H. Brunner Consultant for: Novartis, Roche, Pfizer, UCB, Celgene, Regeneron, Amgen, Astrazeneca, GSK, BMS, Speakers bureau: Novartis, Roche, P. Quartier Grant/research support from: Abbvie, BMS, Chugai-Roche, Novartis, Pfizer, SOBI, Consultant for: Abbvie, Novartis, Servier, SOBI, Speakers bureau: Abbvie, BMS, Chugai-Roche, Medimmune, Novartis, Pfizer, SOBI, T. Constantin: None declared, E. Alexeeva Grant/research support from: Roche, Abbott, Novartis, Pfizer, Bristol-Myers Squibb, Centocor, Speakers bureau: Roche, Novartis, Merck Sharp Dohme, Bristol-Myers Squibb, Medac, Pfizer, R. Schneider Consultant for: Novartis, Novimmune, Sobi, Innomar Strategies, I. Kone-Paut Grant/research support from: SOBI, Novartis, Roche, Consultant for: Novartis, SOBI, Pfizer, Abbvie, Roche/Chugai, K. Schikler Consultant for: Novartis, Novimmune, Sobi, Innomar Strategies, K. Marzan Grant/research support from: Novartis, Abbvie, N. Wulffraat Grant/research support from: Novartis, S. Padeh: None declared, V. Chasnyk: None declared, C. Wouters Grant/research support from: GSK, Novartis, Roche, J. Kuemmerle-Deschner Grant/research support from: Novartis, Consultant for: Novartis, SOBI, Baxalta, T. Kallinich: None declared, B. Lauwerys: None declared, E. Haddad: None declared, E. Nasonov: None declared, M. Trachana Grant/research support from: Novartis, Abbvie, Bristol Meyers, Consultant for: Novartis, Roche, Pfizer, O. Vougiouka: None declared, K. Leon Employee of: Novartis, A. Speziale Employee of: Novartis, K. Lheritier Shareholder of: Novartis, Employee of: Novartis, A. Martini Grant/research support from: Abbott, BMS, "Francesco Angelini", GlaxoSmithKline (GSK), Hoffman-La Roche, Italfarmaco, Janssen, Novartis, Pfizer, Sanofi Aventis, Schwarz Biosciences, Sobi, Xoma, Wyeth, Speakers bureau: Abbott, Abbvie, Amgen, Biogenidecm Bristol MyersSquibb, Astellas, Behringer, Italfarmaco, Janssen, MedImmune, Novartis, NovoNordisk, Pfizer, Sanofi, Roche, Servier, Takeda, D. Lovell Grant/research support from: National Institutes of Health, Consultant for: Astra-Zeneca, Bristol Meyers Squibb, AbbVee, Pfizer, Roche, Novartis, UCB, Forest Research Institute, Horizon, Johnson & Johnson, Biogen, Takeda, Genentech, Glaxo Smith Kline, Boehringer Ingelheim, Celgene, Jannsen, Speakers bureau: Genentech, Roche, Novartis